2008
DOI: 10.1111/j.1742-7843.2008.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic Acid Receptors Participate in the Analgesic but Not Hypnotic Effects of Emulsified Halogenated Anaesthetics

Abstract: The present study was designed to investigate the role of α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in hypnosis and analgesia induced by emulsified inhalation anaesthetics. After having established the mice model of hypnosis and analgesia by intraperitoneally injecting appropriate doses of emulsified enflurane, isoflurane or sevoflurane, we intracerebroventricularly or intrathecally injected different doses of AMPA and then observed the effects on the sleep time using hypnosis test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Previous studies support the efficacy and safety of the iv administration of emulsified inhalation anesthetics in animals [34,35]. According to drug pharmacokinetics and our preliminary experiments [6,7], we confirmed that ip and sc injection of emulsified inhalation anesthetics can achieve hypnosis and analgesia similar to that produced by inhalation. In the hypnosis test, hypnotic doses of emulsified sevoflurane induced the loss of mouse righting reflex.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies support the efficacy and safety of the iv administration of emulsified inhalation anesthetics in animals [34,35]. According to drug pharmacokinetics and our preliminary experiments [6,7], we confirmed that ip and sc injection of emulsified inhalation anesthetics can achieve hypnosis and analgesia similar to that produced by inhalation. In the hypnosis test, hypnotic doses of emulsified sevoflurane induced the loss of mouse righting reflex.…”
Section: Discussionsupporting
confidence: 80%
“…The hypnotic dose of sevoflurane (20 ml/kg) was determined in preliminary experiments [6]. Sevoflurane was injected intraperitoneally (ip) to produce hypnosis in mice.…”
Section: Drug Administrationmentioning
confidence: 99%
“…AMPA receptors contribute to the acute spinal processing of both nociceptive and non-nociceptive inputs in the spinal cord [23,24]. Not only have they been implicated in analgesic action of anaesthetics [25,26], but accumulating evidence indicates that they contribute to synaptic plasticity associated with chronic pain states [27,28]. There is still an ongoing controversy whether xenon inhibits AMPA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…There is also accumulating evidence of the importance of AMPA receptors in analgesic mechanisms associated with anaesthetic and non-anaesthetic drugs – such as xenon [27], halothane [28], and the AMPA antagonist Tezampel [29]. The amygdala is known to be associated with the emotional component of the pain experience [30, 31], and is linked with the paraventricular thalamus [32] in a circuit that modulates the endogenous descending anti-nociceptive pathways [33].…”
Section: Discussionmentioning
confidence: 99%